Fractionation, antioxidant and inhibitory activity of Thai mango seed kernel extracts - Chaianun NAMNGAM; Supakorn BOONYUEN; Praphan PINSIRODOM (My University, 2018)
Mango seed kernel extracts (MSKE) from Kaew and Choke-Anan mango cultivars were fractionated using Sephadex LH-20 column chromatography. Antioxidant activity and the inhibitory effects on tyrosinase, 5-lipoxygenase, hyaluronidase and α-glucosidase of MSKE fractions were evaluated. The key components of polyphenol, found in the most active fraction, were identified using LC-ESI-MS. Three major isolates were obtained from both cultivars of the MSKE with the absorbance being higher for Choke-Anan than Kaew. Fraction 3 of MSKE from both cultivars showed significantly (P ≤ 0.05) higher antioxidant activity and 5-lipoxygenase, hyaluronidase and α-glucosidase inhibitory activity with Choke-Anan more effective than Kaew. Six different polyphenols were found in fraction 3 of both cultivars. These were tri-o-galloyl-glucoside, tetra-o-galloyl-glucoside, maclurin tri-o-galloyl-glucoside, penta-o-galloyl-glucoside, hexa-o-galloyl-glucoside, and hepta-o-galloyl-glucoside. In the MSKE from Choke-Anan, hexa-o-galloyl-glucoside, and tetra-o-galloyl-glucoside were the two major components, whereas in the MSKE from Kaew tetra-o-galloyl-glucoside was the only major component. The results indicate that MSKE is a suitable by-product that could be utilised for adding value to the mango processing industry and could represent a valuable input into functional foods and pharmaceutical production.
Keywords: Glucoside; Sephadex; Hyaluronidase; Phytochemicals and Antioxidant Activities